THE ROLE OF FORENSIC ACCOUNTING IN DETECTING AND PREVENTING FINANCIAL CRIMES IN THE CORPORATE SECTOR - Hidayat, Muhammad; Prasetyo, Eko (Accounting Studies and Tax Journal (COUNT), 2025)
This study aims to evaluate the effectiveness of forensic accounting in detecting and preventing financial crimes in the corporate sector through a forensic approach.narrative reviewsemi-systematic review of the literature from 2010–2025. The results of the synthesis show that the application of forensic accounting supported by strong corporate governance, professional auditor competence, and the use of digital technology such as artificial intelligence and big data analytics significantly improve fraud detection and prevention capabilities. However, its effectiveness is still influenced by contextual factors such as organizational culture, managerial support, and the regulatory environment. Theoretically, this study integrates Agency Theory And Fraud Triangle Theory to explain the role of forensic accounting in reducing agency conflicts and opportunities for fraud. These findings underscore the importance of forensic audits as a preventive and strategic mechanism for strengthening corporate transparency, accountability, and financial integrity.